Highly Sensitive Ratiometric Chemosensor for Selective ′Naked‐Eye′ Nanomolar Detection of Co2+ in Semi‐Aqueous Media. Issue 11 (12th May 2014) - Patil, Smita; Fegade, Umesh; Sahoo, Suban K.; Singh, Amanpreet; Marek, Jaromir; Singh, Narinder; Bendre, Ratnamala; Kuwar, Anil
Abstract An easy‐to‐prepare chemosensor, (E)‐1‐(phthalazine‐4‐yl)‐2‐(1‐(pyridine‐2‐yl)ethylidene) hydrazine (3), structurally characterized by single X‐ray crystallography, is developed for the selective and sensitive detection of Co2+ in aqueous media. Chemosensor 3 shows both absorption and fluorescence responses to Co2+ by forming a 1:1 complex (among the surveyed metal ions) with a detection limit down to 50 nM. It can also be used as a ′naked‐eye′ sensor due to the outstanding visible and emission color changes from yellow to red and blue to orange, respectively.